Nighttime Atomic Hydrogen Abundance Retrieved From SCIAMACHY Hydroxyl Airglow Measurements in the Mesopause Region - Xiaolin Wu; Yajun Zhu; Anne K. Smith; Martin Kaufmann; Jiyao Xu (Geophysical Research Letters)
Abstract Atomic hydrogen (H) is crucial for understanding photochemistry and the energy budget in the mesopause region. However, there is still no consensus on the H abundance in this region. This study presents a new hydrogen data set derived from Scanning Imaging Absorption Spectrometer for Atmospheric Chartography (SCIAMACHY) OH(9–6) band spectra, collocated with temperature and ozone profiles from other remote sensing instruments. H number densities peak at 82–87 km and range from 1.5×108 to 4×108 cm−3, depending on season and latitude. Two other H data sets obtained from the Sounding of the Atmosphere using Broadband Emission Radiometry (SABER) are presented for comparison: those from Mlynczak et al. (2018, https://doi.org/10.1029/2018GL077377) and Panka et al. (2021, https://doi.org/10.1029/2020GL091053) are approximately 30% lower and 50% higher than the SCIAMACHY data at peak altitudes, respectively. Additionally, the H number density retrieved in this study partly shows better agreement with the only direct rocket in situ measurements than those from SABER.